Surfactant-free emulsion electrosynthesis via power ultrasound: electrocatalytic formation of carbon-carbon bonds - Davies, T; Banks, C; Nuthakki, B; Rusling, J; France, R; Wadhawana, J; Compton, R (2002)
Proof-of-concept of the mediated electrosynthesis of carbon-carbon bonds in totally 'green' surfactant-free emulsion media generated by application of power ultrasound to a biphasic water-organic mixture is illustrated by reference to three systems, some requiring further activation by light, and each catalysed by vitamin B12. The voltammetry of aqueous vitamin B12 solutions at an electrode modified with microdroplets of the organic reactant is employed to gain an insight into the electrocatalytic pathway and readily permits the identification of optimum reaction parameters, such as starting material ratios and wavelength of light. The latter are employed in proof-of-concept emulsion electrosynthesis under conditions of triple activation (electron transfer, ultrasound and light).